Plate 10: Agrostemma githago - Fitton, Sarah Mary; Fitton, Elizabeth (Conversations on Botany, 1817)
Hand-colored lithograph of corn cockle, Agrostemma githago. Class Decandria, order Pentagynia.
Keywords: Common corncockle; Botany; Agrostemma; Women botanists; Scientific illustration